Bargaining for gender equality in Aotearoa New Zealand: Flexible work arrangements in collective agreements, 2007–2019. (September 2021) - Proctor-Thomson, Sarah; Donnelly, Noelle; Parker, Jane
Collective bargaining remains an important yet underexplored mechanism in the pursuit of workplace gender equality. Through gender equality bargaining efforts, unions seek to address the lack of equity for working women. Yet little is known of the extent of equality bargaining provisions, or about where provisions and the factors that influence their availability occur. Contributing to this disparity is a lack of data measuring gender equality provisions in collective agreements. This article analyses key trends in the collective regulation of flexible work provisions in Aotearoa New Zealand from 2007 to 2019. Results show modest growth in the scope and coverage of flexible work provisions, the majority of which have occurred in the public sector. Marked differences across sectors and industries suggest the influence of factors such as women's rising labour force participation and feminisation of union membership and its leadership, particularly within industries where union density has grown. Findings underscore the need for contextualisation of collective regulation in opportunity structures and the ongoing frailty of women's access to gender equality.